Seniors don't use Medicare.Gov: how do eligible beneficiaries obtain information about Medicare Advantage Plans in the United States? - Maricruz Rivera-Hernandez; Kristy L. Blackwood; Marquisele Mercedes; Kyle A. Moody (BMC, 2021)
Abstract Background Managed care programs in the US are becoming a preferred alternative among low-income individuals in the US. Every year during open enrollment, seniors can enroll in Medicare Advantage (MA) or switch MA plans. However, there is very limited information about how seniors obtain information to help them make their choices. While the Centers for Medicaid and Medicare offer online resources that are designed to enable potential beneficiaries to make informed coverage decisions, there is no information as to whether seniors use these resources, and therefore whether these resources are effective compared to other information retrieval methods. Methods The purpose of the present study was to qualitatively explore how seniors obtain information about insurance plans in MA. We conducted semi-structured interviews with 26 MA beneficiaries from Rhode Island. Results We found that most seniors have strong preferences for obtaining information in-person regarding benefits, cost and other plan information. Some seniors relied heavily on insurance brokers or representatives, and considered the information provided to them without questioning the potential for bias. Others consulted with family and/or friends for guidance, or to compare costs and benefits. Only a few of these seniors used the available internet resources, and in fact most of them mentioned that they did not have a computer/smart device with internet capabilities. However, among those who used and appeared to be comfortable with navigating the internet, www.medicare.gov was not discussed as a useful resource for making decisions regarding health insurance. Conclusions This study suggests that existing online medical resource usage and effects among senior citizens in the United States may need supplementing with in-person communication among influential agents.